2018
DOI: 10.3389/fpsyg.2018.02187
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Parent–Adolescent Relationships: The Mediating Roles of Behavioral Autonomy and Parental Authority

Abstract: The parent–adolescent relationship has been a classic research topic, and researchers have found that parenting styles (e.g., authoritative, authoritarian) are closely related to various qualities of parent-adolescent relationships (e.g., cohesion, conflict). However, little empirical work has addressed how these variables correlate with each other in mainland China, nor has prior research addressed internal psychological mechanisms. The present study investigated the associations between parenting styles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 42 publications
(91 reference statements)
2
75
0
6
Order By: Relevance
“…Disagreeing Influencers had the largest disparity in proportions of parents and children agreeing with JS-LPA (99% versus 26%, respectively). In a study investigating associations between parenting styles and parent-adolescent relationship factors, both youthreported agreement with legitimacy of parental authority and level of conflict intensity differed by parenting style [30]. Thus, it is possible that the parenting style(s) of Disagreeing Influencers differed from the other classes.…”
Section: Discussionmentioning
confidence: 99%
“…Disagreeing Influencers had the largest disparity in proportions of parents and children agreeing with JS-LPA (99% versus 26%, respectively). In a study investigating associations between parenting styles and parent-adolescent relationship factors, both youthreported agreement with legitimacy of parental authority and level of conflict intensity differed by parenting style [30]. Thus, it is possible that the parenting style(s) of Disagreeing Influencers differed from the other classes.…”
Section: Discussionmentioning
confidence: 99%
“…Effective interaction with adolescents is one of the parenting skills that has been emphasized in optimal parenting styles. Findings from several studies have shown that parents who use the authoritative parenting style with dual characteristics of responsiveness (discipline, supervision, control) and demandingness (acceptance, friendliness, support, and parental involvement) raise more successful adolescents [22,23]. On the other hand, authoritarian parents would like their children to obey them and approve and use punitive methods; Permissive parents do not have a clear boundary for desirable and undesirable behaviors and refrain from control.…”
Section: Discussionmentioning
confidence: 99%
“…Disagreeing In uencers had the largest disparity in proportions of parents and children agreeing with JS-LPA (99% versus 26%, respectively). In a study investigating associations between parenting styles and parent-adolescent relationship factors, both youth-reported agreement with legitimacy of parental authority and level of con ict intensity differed by parenting style [30]. Thus, it is possible that the parenting style(s) of Disagreeing In uencers differed from the other classes.…”
Section: Discussionmentioning
confidence: 99%